The prevalence of common mental health problems and associated psychosocial issues in elite swimmers - Harrison Howarth; Guy Evans; Pieter Kruger; Evie Dilkes; Gary Bell; Courtney Kipps (Hogrefe AG, 2023)
Abstract: Introduction: The mental health of elite athletes has been recognised as of great importance. There have been relatively few studies examining the prevalence of mental health problems in swimmers. None have commented on the range of psychosocial problems associated with mental ill-health. The aim of this study was to identify the prevalence of common mental health problems and psychosocial problems in elite swimmers. Methods: The study was conducted on a national swimming squad competing at the international level. All athletes (n=55) were invited to participate. The response rate was 63.3% (n=36). The study was cross-sectional in design. Data was collected using a battery of psychometric tests yielding information on distress (The Distress Screener), anxiety and depression (PHQ-9, K10), sleep disturbance (PROMIS scale), alcohol consumption (AUDIT-C), smoking behaviour, adverse nutrition behaviour, career satisfaction (Career Satisfaction Scale) and mental toughness (Mental Toughness Index). Results: The prevalence of depression was 14% (n=5). Six percent (n=2) reported suicidal ideation in the last 2 weeks. Fourteen percent met criteria for distress. There were positive correlations between depression and sleep disturbance (r=.343, p<.05), between anxiety/depression and distress (r=.380, p<.05), and between depression and distress (r=.531, p<.01). Career dissatisfaction was identified in 46% of participants and was inversely correlated with mental toughness (r=.485, p<.01). Low mental toughness and adverse alcohol use were identified in 37% and 23% of participants, respectively. Conclusions: Elite swimmers experience common mental illnesses and associated psychosocial problems. There is a relationship between career dissatisfaction and low mental toughness. Sport governing bodies should assess their own athlete populations and implement programmes to support mental health.